Always somehow in the back of the mind. Gender equality education in preschools - Pálsdóttir, Sólveig Björg; Jóhannesson, Ingólfur Ásgeir (Netla, 2020)
The aim of the study was to explore the practice of gender equality education in the oldest age groups in Icelandic preschools. Seven preschool teachers in six preschools in the capital city area were interviewed, and the researcher conducted around three hours of observation in each of the schools to gain insight into classroom practice. The sample of schools and teachers was determined by employing a stratified random sampling, from different parts of Reykjavík and its surrounding towns. The interviews were rich in content and observations insightful into daily operations at the preschools.The findings are reported here in three thematic groups. The first group contains four main themes: How the children dress, role models, stereotypes about sex roles, and gender division. The interviewees reported on the ways in which the gendered and gender-divided society tends to be reflected in preschool operations. This appears, for example, in the gendered dress code of the children which may be influenced by popular children’s television programs. The preschool teachers were critical of gender stereotypes in society, and they expressed the view that if more men worked in preschools, a greater variety of role models would be presented to the children. The preschool teachers were also critical of how gender was constructed among the children and argued that they had the role of fostering critical thinking in the children.The second group comprises six themes: Books, what appeared on the walls, blocks, jigsaw puzzles, role play, and rough and tumble play. The interviewees emphasized the importance of scrutinizing books according to the type of gender images and stereotypes they present. When posters and wall art in the schools were examined, examples of stereotypes were not typical. The blocks were considered to be gender divided-toys in spite of being “unbelievably ungendered phenomena”, as one of the teachers put it. In their experience, boys played more with blocks than girls did. The teachers are conscious of gendered ...